PEREMPUAN DAN AKTUALISASI - Hayail Umroh (Takammul : Jurnal Studi Gender dan Islam Serta Perlindungan Anak, 2018)
Women are part of society. If people ignore them this means ignoring the society. Self-actualization as a form of manifestation of the creative potential of women is something that every woman should have. Because nowadays women have higher education and have an extensive knowledge, they should have been able to apply what they have known into tangible forms. Women also have many useful skills. Therefore, there are no more reasons to restrict their activities. Restrictions on women's self-actualization is a form of castration for women's rights. For this, the opportunity and the support from their family, especially from their husband are indispensable.